Sobre a hibridação natural em Phaseolus vulgaris L. - Vieira, Clibas (Revista Ceres, 2024)
In order to verify the frequency of natural hybridization in the common bean, two varieties were planted in alternated rows, at two different planting times. In the so-called «dry season», in 1958-1959, 0,18% natural hybrids were fouad, and in the so-called «rainy season» of the following year there were 0,70%. It appears that insects of the order Thysanoptera — the thrips — are the field cross-pollination vectors.